Field evaluation of reflective insulation in south east Asia - Teh, Kharsan; Yarbrough, David W.; Lim, Chinhaw; Salleh, Elias (De Gruyter Open Ltd., 2017)
The objective of this research was to obtain thermal performance data for reflective insulations in a South East Asia environment. Thermal resistance data (RSI, m2 K/W) for reflective insulations are well established from 1-D steady-state tests, but thermal data for reflective insulation in structures like those found in South East Asia are scarce. Data for reflective insulations in South East Asia will add to the worldwide database for this type of energy-conserving material. RSI were obtained from heat flux and temperature data of three identical structures in the same location. One unit did not have insulation above the ceiling, while the second and third units were insulated with reflective insulation with emittance less than 0.05. RSI for the uninsulated test unit varied from 0.37 to 0.40 m2 K/W. RSI for a single-sheet reflective insulation (woven foil) varied from 2.15 to 2.26 m2 K/W, while bubble-foil insulation varied from 2.69 to 3.09 m2 K/W. The range of RSI values resulted from differences in the spacing between the reflective insulation and the roof. In addition, the reflective insulation below the roof lowered attic temperatures by as much as 9.7° C. Reductions in ceiling heat flux of 80 to 90% relative to the uninsulated structure, due to the reflective insulation, were observed.